International Humanitarian Law under Pressure: Legal Responses to 21st Century Armed Conflicts - Hermansyah (Legalis : Journal of Law Review, 2024)
This narrative review explores the evolution of International Humanitarian Law (IHL) in the context of contemporary armed conflicts, focusing on five key areas: technological innovation, gender-based protection, humanitarian intervention, urban warfare, and non-state actors. The study begins by framing the urgency to reevaluate IHL as conflicts become increasingly complex due to technological advancement and hybrid threats. The literature was collected from databases such as Scopus and Google Scholar using specific keywords including "autonomous weapons," "urban warfare regulations," and "non-state actors in armed conflict." Peer-reviewed articles published from 2000 onwards formed the basis of the analysis. The results reveal multiple gaps between existing legal frameworks and the realities on the ground. Technological developments such as drones and AI challenge core principles of distinction and proportionality. Gender-focused instruments like CEDAW and UNSC Resolution 1325 have enhanced protections but suffer from inconsistent implementation. The Responsibility to Protect (R2P) doctrine introduces ethical and legal tensions regarding sovereignty, with mixed success in cases like Libya and Rwanda. Urban warfare and sieges demonstrate IHL's difficulty in regulating densely populated battlegrounds. Non-state actors complicate legal accountability due to their diverse structures and cross-border operations. The discussion emphasizes the role of systemic legal constraints and advocates for reforms that reflect current military practices. This review concludes that advancing legal adaptability, international cooperation, and contextualized policy interventions is vital to ensure effective civilian protection and uphold humanitarian norms in modern warfare.